Fundamental aspects of functional grading via powder hot isostatic pressing – Development of microstructure and diffusional processes. (March 2022) - Stavroulakis, Emmanouil; Irukuvarghula, Sandeep; Pickering, Ed; Stewart, David; Preuss, Michael
Graphical abstract: Mixed austenitic and ferritic steel powders consolidated via the hot isostatic pressing process present a bimodal microstructure and interesting properties. Highlights: Functional grading by hot isostatic pressing of mixed austenitic and ferritic steel powders has been studied. Joining dissimilar metal components while minimising excessive grain growth has been achieved via the hot isostatic pressing. Diffusional processes during hot isostatic pressing at various temperatures have been comprehensively investigated. Significant increase in hardness only with a limited lath constituent in a soft austenitic matrix achieved. A model has been proposed for predicting the microstructure of mixed powder specimens depending on the processing conditions. Abstract: Functional grading of a ferritic steel (SA508 grade 3) and austenitic stainless steel (316L) powder via hot isostatic pressing (HIP) consolidation is investigated as an alternative to dissimilar welding. Fundamental aspects of this method such as the development of microstructure and diffusional processes during the HIP process of such mixed powder are studied in this work. A change of the post-HIP α to γ ratio with HIP temperature was observed in mixed powder specimens, combined with the formation of a ferritic lath zone which affects the properties of the specimens (throughout this work the term ferritic laths refers to a ferritic phase of unknown structure which is likely to consist of martensite, bainite or a mixture of both). These effects were attributed to extensive diffusion of alloying elements from 316L into SA508 grade 3. Simulation and experimental quantification of diffusion in diffusion couple experiments were applied to derive an empirical model for estimating α-Fe boundary migration and the formation of the ferritic lath zone and phase fractions for various temperatures and dwell times of the HIP process.